Comparative calculation of the fuel-optimal operating strategy for diesel hybrid railway vehicles - Leska, Maik; Aschemann, Harald; Melzer, Michael; Meinert, Michael (Zielona Góra: Uniwersytet Zielonogórski)
In contrast to road-based traffic, the track as well as the corresponding duty cycle for railways are known beforehand, which represents a great advantage during the development of operating strategies for hybrid vehicles. Hence the benefits of hybrid vehicles regarding the fuel consumption can be exploited by means of an off-line optimisation. In this article, the fuel-optimal operating strategy is calculated for one specified track using two hybrid railway vehicles with different kinds of energy storage systems: on the one hand, a lithium-ion battery (high-energy storage) and, on the other, a double layer capacitor (high-power storage).
Keywords: hybrid railway vehicle; fuel-optimal energy management; dynamic programming; sensitivity; optimisation